Demographics, comorbidities, and outcomes among young and middle-aged COVID-19 patients in Saudi Arabia - Amer S. Alali; Abdulaziz O. Alshehri; Ahmed Assiri; Shahd Khan; Munirah A. Alkathiri; Omar A. Almohammed; Waleed Badoghaish; Saeed M. AlQahtani; Musaad A. Alshammari; Mohamed Mohany; Faisal F. Alamri; Yazed AlRuthia; et al. (Saudi Pharmaceutical Journal)
The impact of different sociodemographic and clinical characteristics on the COVID-19-related morbidity and mortality rates have been studied extensively around the world; however, there is a dearth of data on the impact of different clinical and sociodemographic variables on the COVID-19-related outcomes in Saudi Arabia. This study aimed to identify those at high risk of worse clinical outcomes, such as hospitalization and longer length of stay (LOS) among young and middle-aged adults (18 to 55 years). In this questionnaire-based cross-sectional study, 706 patients with real-time polymerase chain reaction (RT-PCR) confirmed COVID-19 infection were interviewed. Patients’ demographic characteristics, dietary habits, medical history, and lifestyle choices were collected through phone interviews. Patients with chronic health conditions, such as diabetes and hypertension, reported a higher rate of hospitalization, ICU admission, oxygen-support needs, and a longer period of recovery and LOS. Multiple logistic regression showed that diabetes, hypertension, and pulmonary disease (e.g., asthma and chronic obstructive pulmonary disease (COPD)) were associated with a higher risk of hospitalization and longer LOS. Multiple logistic regression showed that symptoms of breathlessness, loss of smell and/or taste, diarrhea, and cough were associated with a longer recovery period. Similarly, breathlessness, vomiting, and diarrhea were associated with higher rates of hospitalization. The findings of this study confirm the similarity of the factors associated with worse clinical outcomes across the world. Future studies should use more robust designs to investigate the impact of different therapies on the COVID-19-related morbidity and mortality in Saudi Arabia.